2020
DOI: 10.1002/lary.29244
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Tonsillectomy Hemorrhage and the Diagnosis of Occult Pediatric Coagulopathies

Abstract: Objectives/Hypothesis: The primary objective of this investigation was to determine rates of abnormal coagulation panels and diagnoses of coagulopathies in children with post-tonsillectomy hemorrhage (PTH). Secondary objectives identified patient demographics and hemorrhage event characteristics that correlated with a coagulopathy diagnosis.Study Design: Case series with chart review. Methods: Patients requiring operative control of PTH at a tertiary children's hospital between 2015 and 2019 were included. Det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…The addition of this key action statement highlights current trends aimed at improving surgical quality and outcomes. During the iterative process of writing the guideline, nonotolaryngologists were surprised to learn that many otolaryngologists do not know their individual or institutional posttonsillectomy bleeding rates . A challenge to knowing this information is the difficulty with capturing posttonsillectomy bleeding occurrences.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of this key action statement highlights current trends aimed at improving surgical quality and outcomes. During the iterative process of writing the guideline, nonotolaryngologists were surprised to learn that many otolaryngologists do not know their individual or institutional posttonsillectomy bleeding rates . A challenge to knowing this information is the difficulty with capturing posttonsillectomy bleeding occurrences.…”
Section: Discussionmentioning
confidence: 99%
“…Con respecto a las indicaciones preoperatorias, destaca que la gran mayoría (94%) de los encuestados solicita hemograma y pruebas de coagulación previo a la cirugía. Esta práctica ha sido cuestionada en estudios recientes, dado que no es considerada costo efectiva, por la relativa baja incidencia de las coagulopatías, asociado al bajo rendimiento de estos exámenes para su diagnóstico 18 . Probablemente, a pesar de ser cuestionado por no ser costo efectiva, es una herramienta que creemos importante como respaldo médico legal, en caso de enfrentarse a un sangrado posoperatorio.…”
Section: Discussionunclassified
“…In 2020, a case series that included a chart review of 250 children with PTH attempted to define the rate and identify characteristics of post tonsillectomy bleeding that would lead to a diagnosis of occult coagulopathy. 9 The authors found that even in children presenting with multiple episodes of post tonsillectomy bleeding, a diagnosis of coagulopathy was rarely uncovered. In the 250 children presenting with PTH, only three were diagnosed with an occult coagulopathy (13%).…”
Section: Surgical and Patient Risk Factorsmentioning
confidence: 99%